2023
DOI: 10.3390/foods12102047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sprouting on Biomolecular and Antioxidant Features of Common Buckwheat (Fagopyrum esculentum)

Abstract: Buckwheat is a pseudo-cereal widely grown and consumed throughout the world. Buckwheat is recognized as a good source of nutrients and, in combination with other health-promoting components, is receiving increasing attention as a potential functional food. Despite the high nutritional value of buckwheat, a variety of anti-nutritional features makes it difficult to exploit its full potential. In this framework, sprouting (or germination) may represent a process capable of improving the macromolecular profile, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Also, various research groups have shown how technological processes, such as sprouting, fermentation, exogenous enzyme treatment, and thermal processing, can lead to an increase in the content of free (and thus more easily extractable) polyphenols in CBW, as well as facilitate the release of bioactive peptides from CBW proteins. 42,89–91 These results emphasize the importance of addressing the role of technological processes in determining the overall bioactivity of foods. Investigation on this topic is currently undergoing novel popularity, also because of the increasing interest in: (i) advanced and sustainable methods for implementing optimal nutritional characteristics using bioprocesses and bio-processed ingredients; (ii) ongoing change in consumer needs, preferences, and expectations; (iii) of the impact of climate changes on the availability (and processing characteristics) of both established and novel plant-based raw materials.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Also, various research groups have shown how technological processes, such as sprouting, fermentation, exogenous enzyme treatment, and thermal processing, can lead to an increase in the content of free (and thus more easily extractable) polyphenols in CBW, as well as facilitate the release of bioactive peptides from CBW proteins. 42,89–91 These results emphasize the importance of addressing the role of technological processes in determining the overall bioactivity of foods. Investigation on this topic is currently undergoing novel popularity, also because of the increasing interest in: (i) advanced and sustainable methods for implementing optimal nutritional characteristics using bioprocesses and bio-processed ingredients; (ii) ongoing change in consumer needs, preferences, and expectations; (iii) of the impact of climate changes on the availability (and processing characteristics) of both established and novel plant-based raw materials.…”
Section: Discussionmentioning
confidence: 84%
“…According to the same study, flavan-3-ols such as epicatechin-3-(3′′-O-methyl) gallate, epicatechin-O-3,4-dimethyl gallate, and catechin-glucoside were the most abundant species in CBW. 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the pre-treatments proposed to enhance the sensory traits of buckwheat, in a previous study we showed that pre-gelatinization treatment was effective in decreasing the bitterness and astringency of both tartary and common buckwheat flour [14]. Since germination produces dramatic changes in the phenolic profile of buckwheat seeds, enhancing the antioxidant potential of the derived products [15][16][17], modifications in the sensory traits of sprouted buckwheat are likely expected and are explored in the present study.…”
Section: Introductionmentioning
confidence: 82%
“…Therefore, buckwheat germination is widely used to improve the compositional properties of grain material. All this will contribute to the use of sprouted buckwheat as a high-quality ingredient in innovative products of industrial interest [6].…”
Section: Introductionmentioning
confidence: 99%